Meningkatkan Kemampuan Mengenal Nilai Mata Uang Melalui Metode Roleplaying - Pajariah, Pajariah; Sopandi, Asep Ahmad (Jurnal Penelitian Pendidikan Khusus, 2022)
The provision of lessons to recognize the value of currency for mildly impaired people aims to describe learning change strategies using the Role Playing method to increase the identification of currency values of denominations of Rp. 100, Rp. 200, Rp. 500, Rp. 1,000, Rp. 2,000, Rp. 5,000, Rp. 10,000 for children with mild mental disabilities. This type of research is classroom action research ( Classroom Action Reseach) using the Role Playing method. This study was conducted in two cycles, with the subjects of students with mental disabilities in the light category of class IV at SLBN Padangsidimpuan 3 students with the initials AH, RAT, RAG. This research is carried out in two cycles consisting of four stages, namely planning, implementation, observation and reflection. The data collection methods used are non-test and test. Non-test data can be obtained from observation sheets and notes in the field, while the test is in the form of questions. From the results of the study obtained, the increase in learning outcomes mngenal meta-money value with the Role Playing method, namely the initial ability of students from AH 36%, RAG 41%, RAT 36% then given action in cycle I increased to AH 60%, RAG 65%, RAT 60%, then continued in cycle II the child's ability increased to AH 85%, RAG 80%, and RAT 80%.